Tinjauan Yuridis Kedudukan Anak Angkat Terhadap Harta Warisan Orang Tua Angkat Perspekrif Hukum Adat (Studi Kasus Di Pengadilan Negeri Klaten) - Mulyono, Joko, Septarina Budiwati, S.H.,M. H., Nuswardhani, S.H.,S.U (2015)
The aim of this research is to know how the legal status of adopted child to foster parents of an inheritance In terms of adopting child and get to know the judge consideration in determining the law in a verdict against the estate of inheritance dispute. This research using methods juridical sociological approach and using qualitative approach. Descriptive type research. The method of analysis of the data used by the writer is a method of a qualitative approach. In existence of this child adopting is not dissever familal relationships between them, which is between adopted child with his biological parents but strengthen familial relationships Because generally child who was adopted is Still have a relationship of blood or familial relationship with a foster parents. Child Adopts which happened in the district court klaten give rise to the existence of a kind of relationship which is reciprocal between them which is that of the adopted child with a foster parents in law heir. In the process of the inheritance of acquired , a child that occurred in the district court Klaten is not limited only inherited combined riches but because of a particular thing may be inherited the origin of a foster parents, although this rarely occurs in district court klaten. Against riches of his biological parents he had a notch same as their biological children in their family. Foster child is entitled to combined riches of foster parents , as an example in decision of district court klaten number 73/PDT.G/1995/PN Klaten.